PENERAPAN METODE EXTREME PROGRAMMING PADA PERANCANGAN APLIKASI POINT OF SALES BERBASIS ANDROID (STUDI KASUS KEDAI KOPI MOKARA) - Heri Setiawan; Susanna Dwi Yulianti Kusuma (CV. Multi Kreasi Media, 2023)
Point of Sale (POS) is a system designed to assist human activities in the sales operations of each transaction process. The coffee shop is one of the business sectors engaged in the food and beverage sector. As well as putting forward a concept, taste and service that has existed for more or less 2 years. The facilities used by the Mokara coffee shop still use a conventional system for recording each employee's absences, sales and purchase transactions as well as recapitulating financial reports so that it runs ineffectively. Therefore we need an application system to simplify and improve the current system. The purpose of this study was to examine the operational system that runs at the Mokara coffee shop, identify existing problems, and develop a system for processing sales transactions and creating financial summary reports. The method used is extreme programming method.